Headache in isolated Wai Wai indigenous people: what’s different? - Honorato, Marcos Manoel; Amorim, Samuel Oliveira de; Pereira, Felipe Henrique Lima; Campos, Bianca Marinho; Padilha, Kelson Vinicius Dallabrida; Maia, Edwagner Coutinho; Moura, Rayssa Oliveira; Ferreira, Matheus da Silva; Nascimento, Ana Flávia Ribeiro; Magalhães, Átila Barros (Headache Medicine, 2024)
Introduction: Headache is a common health condition that affects individuals' quality of life provoking temporary disability.Waiwai form an indigenous group that live in a remote Amazon region. There are 2503 people with no roads connecting to the cities. They live from agriculture, fishing and hunting, eat few processed foods, including sugar, and the diet is low in salt. Objective: To study the headache occurence in people from the Wai Wai tribes and epidemiological and clinical characteristics of indigenous affected. Methods: This is a retrospective, observational and quantitative study based on primary data from medical records of patients treated at the neurology outpatient clinic in Oriximiná, Pará, Brazil (regional reference center for indigenous health). Data from patients from the Wai wai tribe who complained of headaches were included from January 2009 to January 2024, excluding data from illegible medical records. Results: Seventy participants were included, with 78.57% being female. The average age was 31.11±14.09 years, higher among men (34.13±19.33 years). Most participants could not specify the onset of headache episodes (20.00%). Daily headaches were noted (54.28%; n=38). Regarding the characteristics of intensity, type, and location, there was significant difficulty, predominating pulsatile nature (47.14%). Strong intensity (18.57%), and holocranial location (10.00%).The majority of cases were classified as migraine (64.28%) and had follow-up care for less than one year (54.28%). Among those who had follow-up care for more than one year, an average follow-up duration of 5.02±4.11 years was observed ). A lower presence of patients with associated comorbidities was noted (7.5%). Neurological examination was normal in 98.5% and Amitriptiline was the drug more used for prophylaxis (62.85%). There was an improvement in symptoms in 24.28% of patients. Conclusion: Headache affects indigenous people, and daily frequency was higher than general population, despite having different diet and lifestyle. Migraine is the most prevalent type of headache among members of the Waiwai indigenous tribe. However, the significant lack of detailed answers about the characteristics of the headache can have influenced the results. This study is crucial for directing future health interventions aimed at improving the quality of life and well-being of affected individuals.